1993
DOI: 10.1080/09595239300185361
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic hangover and performance: a review

Abstract: The study of alcoholic hangover is reviewed, with particular concern given to its effects upon skills performance. Different models of hangover, and the evidence gathered in their support, are surveyed. Several factors appear to contribute to hangover, and individuals may be differentially susceptible to these influences. The severity of hangover is affected by dose, coproducts of manufacture, and a number of psychological variables. Hangover is differentiated from post-intoxication effects on performance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…Introducing alcohol to the body initiates a number of short-term physiological adaptations including altered neural and endocrine functioning ( Lemon, 1993 ). Hangover is thought to be caused, in part, by re-adaptation processes once alcohol has been fully metabolised and cleared.…”
Section: The Experience Of Hangovermentioning
confidence: 99%
See 3 more Smart Citations
“…Introducing alcohol to the body initiates a number of short-term physiological adaptations including altered neural and endocrine functioning ( Lemon, 1993 ). Hangover is thought to be caused, in part, by re-adaptation processes once alcohol has been fully metabolised and cleared.…”
Section: The Experience Of Hangovermentioning
confidence: 99%
“…In general, the extant research is inconsistent in showing decrements in performance with hangover, prompting Lemon (1993) to state, " it must be noted that for nearly every performance difference found in the post-intoxication state, there is at least one other study using the same, or similar, tests which has reported no effect " (p. 309). Therefore, we can only assume that the delayed effects of alcohol on performance do not substantially differ between females and males.…”
Section: Delayed (Hangover) Effects Of Alcohol Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the acute effects, substance use occurring hours before the beginning of the shift can cause spillover effects, such as fatigue and hangovers that may independently increase the injury risk . In fact, it has been shown that hangovers affect cognitive skills, including tasks related to driving or piloting aircrafts, which may influence the risk of injury in a manner similar to the influences of acute alcohol intoxication …”
Section: Introductionmentioning
confidence: 99%